Social Loafing of Members of the MAPALA Organization in Sidoarjo: Social Loafing Pada Anggota Organisasi MAPALA di Sidoarjo - Liemika, Firma; Maryam, Effy Wardati (Indonesian Journal of Innovation Studies, 2023)
Social loafing is a tendency for individuals to reduce the effort put into achieving a common goal than when work is calculated individually. The purpose of this study was to see the description of social loafing on members of the Mapala organization in Sidoarjo. This research uses descriptive quantitative research and was conducted in Mapala Sidoarjo. The sample in this study were members of the Mapala organization in Sidoarjo as many as 123 respondents. The data collection technique in this study used a social loafing scale in the form of a Likert scale. The results of this study indicate that 64 out of 123 people have social loafing in the high category (52%). The highest social loafing aspect of Mapala organization members is the evaluation apprehension aspect with an average value of 23.46.